(3QSGdI aj GdQVGYs - (3eLghds
(3ChdgG (B:s
(3Gdbhd aj GdQVGY(B. (3hGYde Cfg dG ETcGd aj Cf GdQVGY ehLH dJMQje GdfcGM aj GdLedI cJGHG hSfI eJhGJQI hELeGYG(B...s
(3BNQgG (B:s
(3hbGYOI GdVQQ dG jbJVj LhGR QLhY GdRhL Edi GdcHjQI aj UhQI EQVGYgG GNJjGQG(B... (3hGdMeO ddg ChdG(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3eMeO HGbQs
Keywords: (3abg GdePGgH GdCNQis